2019
DOI: 10.1080/16549716.2019.1596378
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of neurological disorders in Tanzania: analysis of baseline data from sample vital registration with verbal autopsy (SAVVY)

Abstract: Background: Neurological disorders (ND) have a profound consequence on human productivity, quality of life and survival. There are limited data on the burden of ND in Tanzania due to insufficient coverage of civil and vital registration systems. Objectives: This study was conducted to estimate mortality of ND in all ages in Tanzania using data from the Sample Vital Registration with Verbal Autopsy (SAVVY) study. Methods: Multistage random sampling was employed to select 23 districts, 1397 census enumeration ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…We were unable to acquire the SAVVY dataset but extracted estimates from a published study. 22 We excluded the National Panel Survey from further analysis because of the small sample (3357 households; 5 traffic deaths). These data sources have not been used for GBD or GSRSS estimates of road traffic deaths in Tanzania.…”
Section: Methodsmentioning
confidence: 99%
“…We were unable to acquire the SAVVY dataset but extracted estimates from a published study. 22 We excluded the National Panel Survey from further analysis because of the small sample (3357 households; 5 traffic deaths). These data sources have not been used for GBD or GSRSS estimates of road traffic deaths in Tanzania.…”
Section: Methodsmentioning
confidence: 99%
“…The literature review yielded 25 publications with potentially relevant road injury data (online supplemental table A1). Based on a review of the title, abstract and full text, we only identified one study, Levira et al ,24 that provided a nationally representative data estimate of causes of death in Tanzania using verbal autopsy.…”
Section: Resultsmentioning
confidence: 99%
“…Causes of death were determined based on verbal autopsy interviews with next of kin or other caregivers. Microdata from the study were not available to us but estimates of road traffic deaths from SAVVY were reported by Levira et al 24 who estimated that 2.43% (95% CI: 2.01 to 2.84) of all-cause deaths were due to road traffic injuries in 2016. We applied these proportions to GBD estimate of all-cause deaths.…”
Section: Resultsmentioning
confidence: 99%
“…Sixty percent of the deaths were related to epilepsy. Population-based studies of mortality from the LMICs are few but it can be inferred from a meta-analysis of these studies, that the proportionate mortality due to status epilepticus (5-57%) and SUDEP (1-20%) is high 21 . In comparison, studies from HICs have shown that the risk of dying due to status epilepticus and SUDEP are as low as 0.2/1000 and <1.5/1000 people respectively 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we visited the homes of those who had died since the initial screening. During these visits, a neurologist (GS), experienced in verbal autopsy protocols, used the WHO verbal autopsy tool to ascertain the cause/s of death in those who died 20,21 . A family member or someone in the household, who was aware of circumstances surrounding the death provided the information.…”
Section: Field Visits and Assessmentsmentioning
confidence: 99%